Penerapan Strategi Pembelajaran Aktif Tipe The Power of Two untuk Meningkatkan Hasil Belajar Murid pada Mata Pelajaran IPS Kelas IV SD Inpres Talaborong Kecamatan Bajeng Barat Kabupaten Gowa - Irmawati Irmawati; Syarifuddin Cn. Sida; Muliani Azis (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
This type of research is class action research (Class Action Research) which consists of two cycles where each cyle is held in 3 meetings. The research procedure consists of 4 stages in each cycle, namely planning, action, observation, and reflection. The subjects in this study were 26 grade IV students of SD Inpres Talaborong, west Bajeng District, Gowa Regency. The results of study showed that in the first cycle, out of 26 students, only 17 students or around 65,4% met the minimum completeness criteria (KKM). Meanwhile, in cycle II, there were 23 students or around 88,5% who completed it. Based on results of the research above, it can be concluded that application of the power of two type active learning strategy can improve student learning outcomes in social studies class IV SD Inpres Talaborong West Bajeng District Gowa Regency.